2018
DOI: 10.12788/j.sder.2018.041
|View full text |Cite
|
Sign up to set email alerts
|

JAK-STAT signaling pathway inhibition: a role for treatment of various dermatologic diseases

Abstract: Cutaneous inflammatory conditions such as psoriasis, atopic dermatitis, alopecia areata, vitiligo, and connective tissue diseases often remain a challenge to treat. Although there is an in-depth understanding of the clinical presentation of these diseases, much less is known regarding the pathophysiology. This has limited the effective treatment options for patients. A more detailed understanding of the pathogenesis of each disease will lead to newer targeted medications with less morbidity. Though there are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Some genes targeted by deregulated plasma miRNAs were associated with angiogenesis (i.e., VEGF pathway) and adaptive and innate immune responses, and proinflammatory genes, such as IL4R, were also identified. In addition, the JAK/STAT pathway, which is related to autoimmune diseases [44,46], such as psoriasis [45,47,48], was also observed. Plasma miRNA target genes play a role in apoptosis, which is associated with psoriasis pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some genes targeted by deregulated plasma miRNAs were associated with angiogenesis (i.e., VEGF pathway) and adaptive and innate immune responses, and proinflammatory genes, such as IL4R, were also identified. In addition, the JAK/STAT pathway, which is related to autoimmune diseases [44,46], such as psoriasis [45,47,48], was also observed. Plasma miRNA target genes play a role in apoptosis, which is associated with psoriasis pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The JAK/STAT signaling pathway is relevant to autoimmune diseases, which indicates that psoriasis is an autoimmune disease [44]. In addition, JAK/STAT signaling pathway inhibition is used for treating psoriasis [45].…”
Section: Network Analysis Of Deregulated Plasma Mirnas Andmentioning
confidence: 99%
“…In addition, GO analysis has shown that the blue module is predominantly involved in chemokine-mediated and complement receptor-mediated signaling and chemokine activity. Previous researches has confirmed that the plasma, lysosomal, and lytic vacuole membranes may be potential targets for treating sarcomas [55,[57][58][59][60].…”
Section: Discussionmentioning
confidence: 95%
“…[54]. The JAK-STAT signaling pathway transfer signals from cell membrane receptors to the nucleus in sarcoma tumors [55]. It modulate the activity of immune system, especially the fate of helper T cells [56].…”
Section: Discussionmentioning
confidence: 99%
“…В серии открытых исследований установлена эффективность ТОФА при гнездной алопеции, в том числе у пациентов с сопутствующим псориазом [58]. К другим дерматологическим заболеваниям, при которых изучается возможность использования ингибиторов JAK, относятся витилиго, ладонно-подошвенный пустулез, идиопатическая многоформная эритема, кожная красная волчанка, ДМ [58,63,64], генерализованная морфея с эозинофильным фасциитом [65], кожный саркоидоз [66] и др.…”
Section: таблицаunclassified